The use of ice-breaking to overcome students’ speaking anxiety - Restianti, Reska; Rachmawati, Etika; Sugiarto, Bambang Ruby (Universitas Galuh, 2025)
Speaking anxiety is the fear felt by students when speaking English. There are several ways that teachers can deal with student speaking anxiety. One of them is by using ice-breaking which can be done at the beginning, middle, or end of the lesson. This study was conducted to find out how teacher use ice breaking and students’ perceptions about ice breaking in overcoming speaking anxiety. The aim of this study is to find out whether ice breaking can really reduce speaking anxiety felt by students. This study used qualitative method and case study as research design. The participants in this study are one English teacher and 29 students at vocational high school in Ciamis. The data collection used interview and closed-ended questionnaire. The findings of this study are that ice breaking can reduce speaking anxiety experienced by students in the learning process, but has not been able to improve students' public speaking and self-confidence. It can be concluded that ice breaking has a positive impact on the teaching and learning process.